2014
DOI: 10.1093/jac/dku072
|View full text |Cite
|
Sign up to set email alerts
|

Gene editing using a zinc-finger nuclease mimicking the CCR5Δ32 mutation induces resistance to CCR5-using HIV-1

Abstract: ZFNCCR5Δ32 is a specific and efficient tool for the generation of CCR5 knockouts. Its ability to mimic the natural CCR5Δ32 phenotype in the absence of relevant off-site cutting events suggests that ZFNCCR5Δ32 might be safe in clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Owing to the indispensable role of CCR5 for HIV-1 entry and the natural presence of the CCR5 D32 variant, a number of gene editing studies have targeted CCR5 by various approaches (Badia et al, 2014;Holt et al, 2010;Huang et al, 1996;Mussolino et al, 2014;Perez et al, 2008;Saito et al, 2014;Ye et al, 2014). In a recently finished Phase I clinical trial, autologous CD4 + T-cells with CCR5 modified by ZFN showed promise in alleviating the disease condition of some HIV-1 patients (Tebas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the indispensable role of CCR5 for HIV-1 entry and the natural presence of the CCR5 D32 variant, a number of gene editing studies have targeted CCR5 by various approaches (Badia et al, 2014;Holt et al, 2010;Huang et al, 1996;Mussolino et al, 2014;Perez et al, 2008;Saito et al, 2014;Ye et al, 2014). In a recently finished Phase I clinical trial, autologous CD4 + T-cells with CCR5 modified by ZFN showed promise in alleviating the disease condition of some HIV-1 patients (Tebas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated safety and feasibility of ZFN-CCR5-modified autologous CD4 + T cell infusions in HIV-infected patients [31 ]. More recently, an optimized ZFN producing CCR5 modifications within the D32 region has been designed that confers high resistance against CCR5-tropic HIV infection with no significant offtarget activity [32]. Collectively, these studies have established the artificial CCR5 gene disruption by ZFNs systems followed by autologous cell transplantation as a reasonable and promising approach for the development of new strategies for HIV treatment.…”
Section: Host Genome Editingmentioning
confidence: 99%
“…Since the unique and exceptional case of an HIV-1 sterilizing cure of a patient due to bone marrow transplantation with a matched donor homozygote for the CCR5⌬32 mutation (47,48), alternative strategies have aimed to reproduce the CCR5⌬32 phenotype using genome-editing tools. Indeed, ZFNs targeting the HIV coreceptor gene have been successfully developed to generate human CD4 ϩ T cells and human embryonic cell precursors and induce pluripotent stem cells that were refractory to HIV-1 infection in different mouse models (9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ZFN on the PSIP1 alleles was assessed by performing PCR on the region surrounding the ZFN target site, followed by digestion with the Surveyor (CEL-1) nuclease assay (Transgenomic, Omaha, NE, USA), which cleaves DNA heteroduplex formations at the mismatch sites. The generated fragments were resolved by 10% polyacrylamide electrophoresis, as previously described (10,12).…”
Section: Vectorsmentioning
confidence: 99%
See 1 more Smart Citation